Georgia Economic Impact of East-West Highway Phase 2 : Assessing the Impact of East-West Highway Investments on Exports through Gravity Modeling - World Bank (World Bank, Washington, DC, 2016)
The objective of this study is to assess the impact of the East-West Highway improvement program on Georgia’s ability to access international markets. As highlighted extensively in the literature, improving transport infrastructure and the efficiency of the logistics sector can help countries gain competitiveness in international export markets, which can translate into faster economic growth and higher income. This study hypothesizes that investments in the EWH have reduced the cost of shipping Georgian goods to the rest of the world, and such reductions should be more significant for goods transported by road. To estimate the effect of cost reductions generated by improvements in the EWH, a gravity-type model in first-differences has been estimated. The results show that: (i) a 10 percent increase in the length of upgraded road network predicts a 1.1 percent increase in exports transported by road while no significant effect is estimated for exports on other transport modes (rail, sea, and air); (ii) the resulting increase in exports by road was reflected by a decrease in exports transported by sea; (iii) the effect is statistically and economically significant only for customs offices located along the EWH; (iv) only exports of time-sensitive products responded positively and significantly to improvements in the EWH during the 2006-2015 period; (v) upgrading the entire EWH is estimated to generate additional export revenues between USD 776 million and USD 1,466 million. It is important to note that the overall trade generating effect of the investment is expected to be somewhat lower as the results suggest some substitution between road and sea transport, but the overall impact is a significant boost to exports.